Recent research progress on the role of interleukin in glaucoma - WU Linzhi; PAN Xuehui; CHEN Xiaofeng (Yixue xinzhi zazhi)
Glaucoma is the most common cause of irreversible blindness in the world, of which pathogenesis, such as autoimmune mechanism and inflammation theory, has been the focus of research in recent years. Interleukin(IL) is a key cytokine-mediated immunity, and may be involved in the pathogenesis of glaucoma. IL-1, IL-8 and IL-17, as the representative pro-inflammatory cytokines, are involved from the discharge of aqueous humor in the anterior segment to the loss of nerve cells in the posterior segment of the eye. As a pleiotropic cytokine, whether IL-6 plays a positive or negative role in glaucoma is still controversial. Anti-inflammatory factors such as IL- 10, IL-4 and IL-13 can protect retinal ganglion cells. This paper reviews the literature on the relationship between IL and glaucoma in recent years, hoping to provide the theoretical basis for the follow-up study on the pathogenesis of glaucoma and the development of new drugs.